2017
DOI: 10.14814/phy2.13082
|View full text |Cite
|
Sign up to set email alerts
|

Maternal high‐fat diet in mice leads to innate airway hyperresponsiveness in the adult offspring

Abstract: Maternal obesity prior to and during pregnancy has been associated with an increased incidence of childhood asthma. As diets rich in saturated fat are linked to obesity and inflammation, we created a murine model to investigate the effect of maternal high‐fat diet (HFD) on adult offspring airway hyperreactivity (AHR), a cardinal feature of asthma. Balb/cByJ dams were fed a HFD (60% fat Calories) or normal‐fat diet (NFD) (10% fat Calories) from 8 weeks prior to first breeding through their pregnancies. Pups wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 40 publications
(71 reference statements)
4
10
2
Order By: Relevance
“…However, we cannot rule out that the changes we observe in NFB-related proteins are not because of the influence of the increased number of macrophages rather than from lung tissues. Our data agree with that reported by Song et al (28) in rat pups exposed to maternal HFD with greater numbers of inflammatory cells within the lung tissues and with MacDonald et al (22) in Balb/cByJ mice exposed to maternal HFD with elevated lL-6 levels and increased numbers of neutrophils in the bronchoalveolar lavage fluid. Furthermore, Zabolotny et al (34) reported that increases in TNF␣ expression activates the NFB p65 subunit, which in turn, binds to the promoter of PTP1B and induces its expression both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, we cannot rule out that the changes we observe in NFB-related proteins are not because of the influence of the increased number of macrophages rather than from lung tissues. Our data agree with that reported by Song et al (28) in rat pups exposed to maternal HFD with greater numbers of inflammatory cells within the lung tissues and with MacDonald et al (22) in Balb/cByJ mice exposed to maternal HFD with elevated lL-6 levels and increased numbers of neutrophils in the bronchoalveolar lavage fluid. Furthermore, Zabolotny et al (34) reported that increases in TNF␣ expression activates the NFB p65 subunit, which in turn, binds to the promoter of PTP1B and induces its expression both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 93%
“…6C). Again, this is different than the PFTs reported in rat pups exposed to maternal obesity and the studies in the Balb/cByj mice (3,22). In rats, PFT increases in pressure volume loop area and decreases in compliance were observed in response to streptozotocin treatment, but no differences were observed because of diet alone.…”
Section: Discussioncontrasting
confidence: 75%
“…We have found no differences in leukocytes in BAL when comparing SC/SHAM to HFD/SHAM mice. This is in apparent contrast to the study published by MacDonald et al [18]. Those researchers found increased leukocytes in BAL of mice born to HFD-fed mice.…”
Section: Discussioncontrasting
confidence: 97%
“…Human studies have shown that maternal obesity during pregnancy and increased gestational weight gain were positively associated with the risk of childhood asthma [16,17]. In accordance with those findings, it was also described that non-allergen-sensitized mice and rats born to mothers exposed to HFD during pregnancy and lactation spontaneously develop lower respiratory system compliance and higher respiratory system resistance [18,19]. Similar data were found in adult non-allergen-sensitized offspring of mice breastfed by dams consuming HFD [20].…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation